FOREIGN EXPERIENCE OF LINGUISTIC SELF-EDUCATION (SECOND HALF OF THE 20TH CENTURY) - Oleksandr L. Shums'kyi (Alfred Nobel University Publisher, 2021)
The paper provides a retrospective analysis of foreign experience of linguistic self-education in the second half of the 20th century. It is shown that reaching the current level of students' training for life-long linguistic self-education requires understanding of socio-historical, pedagogical and practical experience, which reveals the logic of development and formation of linguistic self-education as an educational phenomenon, as well as determinants and factors which have been influencing this development. Having studied a wide range of sources, we can state that the issues concerning self-education have always been topical problems of scientific knowledge. However, for many centuries in the world pedagogical theory and practice linguistic self-education as such was not regarded as a separate pedagogical phenomenon, but instead, it was only the applied and general educational value of learning foreign languages which was taken into consideration. We have defined that the essence and forms of linguistic self-education depending on historical, economic, political and social factors changed in different years and determined both by the logic of educational development in general and the needs of the society as whole as well as certain individuals to master foreign languages. The period from the middle of the 20th to the beginning of the 21st century became a revolutionary stage in the development of the theory and practice of foreign language self-education. We found that the impetus for the intensive development of a methodology for adults' self-instruction in foreign languages was the historic events of World War II. The method of "on-the-spot linguistic analysis" was introduced. This method became the basis for special research on autonomous learning of foreign languages by adults, and later - for linguistic self-education. In the 50-60s of the 20th century, foreign language and sociocultural training was first recognized at the international legislative level. Audiolingual and audiovisual methods became widespread back then. In the 70s and 80s of the 20th century, theoretical developments and practical experience in the field of independent study of foreign languages, as well as singling out the concept of "autonomous learning" as a separate pedagogical category became a driving force for the formation and development of linguistic self-education. Since the 80s of the 20th century, along with the theoretical developments, the practice of foreign language self-education has been actively developing and improving. In the present-day system of higher education in Western countries, self-educational activities in learning foreign languages are equated to traditional organizational forms of educational activities. At the beginning of the 21st century, the innovative methods of self-instruction of foreign languages are gradually being introduced into the educational process at a number of European universities. Thus, having implemented the retrospective analysis of foreign experience in foreign language selfeducation we can conclude that in the second half of the 20th century important prerequisites were created for distinguishing the concept of linguistic self-education into a separate category of language didactics and a specific type of educational activities.